When Katie's Parents Separated - York, Sarah Mountbatten-Windsor, Duchess of Duchess of, 1959-; Cunliffe, Ian (New York : Sterling, 2011)
Katie learns that there are both good and bad things about her parents no longer living together.
Originally published: When Katie's mum and dad separated. Coventry : Lloyds Pharmacy, 2007.
Keywords: Separation anxiety in children -- Fiction; Parent-child relationship -- Fiction; divorce